Strategi Peningkatan Responsivitas Satuan Polisi Pamong Praja Jawa Timur Dengan Analytical Hierarchy Process - Muhamad Hadi Wawan Guntoro (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
The existence of technological developments which have an impact on increasing community needs causes Satpol PP as a Public Service Agency to have to improve the quality of its services. One indicator of improving service quality can be seen from organizational responsiveness. The aim of this research is to analyze the order of Priority Aspects and Criteria for the Influence of the Responsiveness and analyze strategies for increasing the Responsiveness of the East Java Civil Service Police Unit. This research is a quantitative descriptive research with data analysis techniques using the Analytical Hierarchy Process (AHP) method with Expert Choice Software. The research population is members of the Satpol PP, determining the number of samples using the Total Sampling method so that the number of samples is the same as the population, namely 14 respondents. The data collection method uses a questionnaire distributed to research respondents. The results of the research prove that the priority order of factors influencing Satpol PP's responsiveness is the Readiness Aspect, Response Aspect and Friendly Aspect with the Priority Aspect being the Readiness Aspect. The order of priority of the criteria for the friendliness aspect is the familiarity criterion, the friendly criterion and the pleasure criterion. The order of priority of criteria in the response aspect is attitude criteria, participation criteria and perception criteria. The priority order of criteria in the readiness aspect is responsibility criteria, knowledge criteria and skills criteria. The strategy to increase the Responsiveness of Satpol PP is to prepare Satpol PP personnel to be able to serve the community responsively through providing training, periodic competency tests for members and monthly evaluations, establishing good relations with the community, especially with sub-district heads, implementing operational standards, and Community service procedures